2022
DOI: 10.3390/app12094215
|View full text |Cite
|
Sign up to set email alerts
|

The Physicochemical Properties, Volatile Compounds and Taste Profile of Black Garlic (Allium sativum L.) Cloves, Paste and Powder

Abstract: Black garlic is produced as a result of the so-called “fermentation processes” of whole heads or cloves kept under controlled conditions of temperature and humidity for several weeks. During this long-term heat treatment, garlic undergoes enzymatic and non-enzymatic browning reactions, which greatly change its taste, aroma, physicochemical, organoleptic and bioactive properties. Black garlic is most often produced in the form of cloves, and recently also in the form of paste and powder. This work focused on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 70 publications
0
16
0
2
Order By: Relevance
“…As reported by Kim et al [ 7 ], the compounds in black garlic have a destructive effect on bacteria (among others, on Staphylococcus , Streptococcus , Salmonella , Escherichia , Klebsiella , Proteus , Helicobacter , Mycobacterium , and Clostridium ), protozoa ( Entamoeba histolytica ) and fungi ( Candida albicans , Saccharomyces cerevisiae , Pichia anomala , Hanseniaspora valbyensis , and Aspergillus niger ). Of particular importance is allicin, which penetrates into the cell and interacts with cytoplasmic components and enzymes; this compound also blocks lipid and RNA synthesis in bacteria [ 6 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported by Kim et al [ 7 ], the compounds in black garlic have a destructive effect on bacteria (among others, on Staphylococcus , Streptococcus , Salmonella , Escherichia , Klebsiella , Proteus , Helicobacter , Mycobacterium , and Clostridium ), protozoa ( Entamoeba histolytica ) and fungi ( Candida albicans , Saccharomyces cerevisiae , Pichia anomala , Hanseniaspora valbyensis , and Aspergillus niger ). Of particular importance is allicin, which penetrates into the cell and interacts with cytoplasmic components and enzymes; this compound also blocks lipid and RNA synthesis in bacteria [ 6 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the Maillard reaction, which occurs during fermentation, increases the concentration of total phenolic acid, flavonoids, 5-hydroxymethylfurfural, melanoidins and thiosulfinates in black garlic [ 2 , 3 , 9 , 11 ]. The fermentation process leads to a decreased pH of the garlic as well as decreased moisture content, thus increasing its shelf life [ 12 , 13 , 14 ]. Fermentation not only affects the basic composition or physicochemical properties of garlic, but also increases the concentration of biologically active compounds [ 4 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The compounds 2-octanone and 2decanone were also identi ed (~ 0.01 mg/mL). In black garlic (Allium sativum L.), the compound 2octanone has already been identi ed by Najman et al (2022), who reported that this volatile could be detected due to aging. The authors attributed that this substance can contribute to the roasted, burnt, caramelized, green, and fruity aroma.…”
Section: Volatile Composition Of Roe Headspace By Gc-ms (Hs-spme-gc-ms)mentioning
confidence: 98%
“…The VOCs 2-octanone and 2-decanone were also identified (∼0.01 mg/mL). In black garlic (Allium sativum L.), 2-octanone has already been identified by Najman et al (2022), who reported that its presence could be due to its aging process. The authors stated that this substance can contribute to the roasted, burnt, caramelized, green, and fruity aroma.…”
Section: Volatile Composition Of Roe Headspace By Gc-ms (Hs-spme-gc-ms)mentioning
confidence: 98%